Back Cover: A High‐Pressure NMR Probe for Aqueous Geochemistry (Angew. Chem. Int. Ed. 37/2014). Issue 37 (22nd July 2014) - Pautler, Brent G.; Colla, Christopher A.; Johnson, Rene L.; Klavins, Peter; Harley, Stephen J.; Ohlin, C. André; Sverjensky, Dimitri A.; Walton, Jeffrey H.; Casey, William H.
<x xml:space="preserve">Abstract</x> Geochemical models for aqueous solution equilibria extend to pressures and temperatures well beyond experimental spectroscopies that could test the predictions. W. H. Casey and co‐workers describe in their Communication on page 9788 ff. a simple NMR probe that can allow spectroscopy on solutions at pressures near those of the Earth's continental crust. (Greg Pautler Graphic Design, Ontario, Canada, is thanked for designing and donating the artwork.)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>